Sistem Informasi Akademik Berbasis Web Pada SMPN 20 Bekasi - Fernando B Siahaan; Savira Marsha (Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2018)
SMPN 20 Bekasi is the school of choice in the area of ​​Bekasi but the data processing is still manual so that the information obtained for a long time therefore required web-based academic information system to produce information quickly and precisely. The purpose of this study is to produce information to school stakeholders, namely the school and students about the learning activities undertaken, assessment and report. Research method used is waterfall technique that is planning, analysis, design, implementation and maintenance. Discussion of this research from the use case diagrams and activity diagrams, entity relationship diagrams and table specifications. In conclusion web-based academic information system is useful for the school, especially teachers in presenting data such as student scores more effectively.